(untitled) (Chemical Engineering Research Bulletin, 2023)
The post-harvest agricultural residue burning in Indo-Gangetic Plains (Punjab, Haryana), starting at the end of October and November, raises severe air pollution problems for the regional areas. Due to the proximity to India, border areas of Bangladesh have a high chance of getting air pollutants with the transported air masses from these regions because of favourable wind directions. This study took Rajshahi as the study area for identifying transboundary air pollution from the Indo-Gangetic Plains (IGP). During the study period (October to December 2018) PM 2.5 and PM 10 concentrations (95±32.5 μg/m3 and 195.4±71.6 μg/m3 respectively) were around 2 times and 1.5 times higher than NAAQS. The satellite-based fire counts from FIRMS showed a high number of fire incidents (>6000) mainly occurred from 27 October to 8 November and Bangladesh has lower than 200 throughout the period. Daily 96 hours of air mass back trajectory and cluster analysis using the HYSPLIT-5 model resulted in 5 clusters for the study period. The C1 and C2 are identified as the main contributors to transboundary air pollution in Rajshahi. The clusters C1 and C2 mainly carried air masses with PM 2.5 from IGPs, Uttar Pradesh, and Delhi and contributed to an increase of more than 35% of PM 2.5 concentration during the crop burning period. Chemical Engineering Research Bulletin 23(2023): 10-16